Influence of puerperium on the serum proteins of Saanen goats, obtained by the analysis of electrophoresis on sodium dodecyl sulphate-polyacrylamide gel / Influência do puerpério sobre o proteinograma sérico de caprinos da raça Saanen obtido por eletroforese em gel de poliacrilamida - Eduardo Harry Birgel Junior; José Jurandir Fagliari; Samantha Ive Miyashiro; Carolina Zaghi Cavalcante; Fabio Celidonio Pogliani; Daniela Becker Birgel; Regiane Machado de Souza; João Paulo Elsen Saut (Semina: Ciências Agrárias, 2009)
Aiming to evaluate the puerperal influence on the proteinogram of Saanen goats, 108 samples of blood serum from 12 goats were collected, and the results were presented at nine times: just after parturition, 1, 3, 5, 7, 10, 15, 21 and 30 days after parturition. Total amount of serum proteins were determined by the biuret technique, and the sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) was used to the protein fractionation. In this last method, 17 protein bands were observed, from which molecular weights varied between 25 KDa and 275 KDa. In addition, it was possible to identify the following protein fractions: immunoglobulin A (180 KDa), ceruloplasmin (115 KDa), transferrin (79 KDa), albumin (65 KDa), heavy-chain immunoglobulin G (58 KDa), haptoglobin (45 KDa), acid glycoprotein (37 KDa) and light-chain immunoglobulin G (28 KDa). Another 9 nonidentified protein fractions presented, each molecular weights equal to 275 KDa, 140 KDa, 125 KDa, 103 KDa, 95 KDa, 41 KDa, 35 KDa, 30 Kda and 25 KDa. The results allow us to conclude that by the first week of puerperium, an improvement of acid glycoprotein occurs, whereas those others protein fractions do not suffer any puerperal influence. Com o objetivo de avaliar a influência do puerpério no proteinograma de caprinos da raça Saanen foram colhidas 108 amostras de soro sangüíneo de 12 cabras, sendo os resultados apresentados em nove momentos: imediatamente após a parição, 1, 3, 5, 7, 10, 15, 21 e 30 dias após o parto. Os teores séricos de proteína total foram determinados pela técnica do biureto, e para o fracionamento das proteínas foi realizada a eletroforese em gel de poliacrilamida contendo dodecil sulfato de sódio (SDS-PAGE). No método utilizado foram observadas 17 bandas protéicas, cujos pesos moleculares (PM) variaram de 25 KDa a 275 KDa, sendo possível a identificação das seguintes frações protéicas: imunoglobulina A (180 KDa), ceruloplasmina (115 KDa), transferrina (79 KDa), albumina (65 KDa), imunoglobulina G cadeia pesada(58 KDa), haptoglobina (45 KDa), glicoproteína ácida (37 KDa) e imunoglobulina G cadeia leve (28 KDa). As outras 9 frações protéicas não identificadas apresentaram pesos moleculares iguais a 275 KDa, 140 KDa, 125 KDa, 103 KDa, 95 KDa, 41 KDa, 35 KDa, 30 Kda e 25 KDa. Os resultados obtidos permitem concluir que durante a primeira semana do puerpério ocorre um aumento das concentrações de glicoproteína ácida, enquanto as demais frações protéicas não sofrem influência do puerpério.